PROFIL BERPIKIR KREATIF SISWA SMP KELAS VIII DALAM MENYELESAIKAN MASALAH SEGIEMPAT DITINJAU DARI GAYA BELAJAR - Ningsih, Egha Fitriyah (Department of Mathematics Education , University of Jember, 2021)
The purpose of this study was to describe the creative thinking profile of grade VIII junior high school students in terms of learning styles in solving quadrilateral problems. This research is a descriptive study using a qualitative approach. The subjects of this research were students VIII A at SMPN 1 Genteng, namely two students from each different type of learning style. Collecting data using questionnaires, test methods, and interview methods. Students' creative thinking is categorized into four indicators, namely fluency, flexibility, originality, and elaboration. The results showed that students in visual learning styles could fulfill all indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. Auditory learning style students can fulfill three indicators of creative thinking, namely fluency, originality, and elaboration.